Facile preparation of rapidly recyclable tough thermosetting composites via cross-linking structure regulation. (17th February 2020) - Xu, Ningdi; Kim, Seulki; Liu, Yingying; Adraro, Yonas Abate; Li, Zhenfen; Hu, Jiangtao; Liu, Li; Hu, Zhen; Huang, Yudong
Abstract: The design and preparation of thermoset materials with high degradation rate and excellent mechanical properties is challenging owing to conflicting attributes of degradability and mechanical properties. Herein, this study introduces an approach to synthesize thermoset materials combining rapid degradability, stability and excellent integrated mechanical properties. The degradable thermoset material is synthesized by using paraformaldehyde (PFA) and aromatic 4, 4'-(1, 3-phenylenedioxy) dianiline (TPE-R) as monomers via aldimine condensation. The degradation rate of thermoset material is significantly enhanced by adjusting the content of hemiaminal structure in hemiaminal dynamic covalent networks (HDCNs). The results demonstrate that the optimized thermoset material represents rapid degradability (4.25 h for totally degradation) at room temperature. Interestingly, the resin still maintains high tensile strength (120 MPa) and excellent thermal stability (Td5%  = 316 °C, Tg  = 174 °C). The thermosetting resin with a combination of great mechanical properties and rapid degradability can be served as materials, which provides a new way to fabricate recyclable thermosetting composites. Graphical abstract: Image 1 Highlights: Novel thermoset with excellent degradability and mechanical properties was fabricated. The degradable rate of PHT can be controlled by cross-linking structure regulation. The recycled CF from composites exhibited the original mechanical strength.